Parenting Types as a Viewed theme in To Kill a MockingBird - Al-Sudairy, Hend T. (Richtmann Publishing, 2012)
Harper Lee's To Kill a Mockingbird (1960) is a novel that is concerened with the parent-child's relationship. One of the thingsthat strikes the reader the most is the bond shared by Atticus, a single parent, and his children Scout and Jim. Most of the lines from thisnovel are memorable and express a lot about parenting in a very simple style. It states that true parenting is about sharing a bond thatprovides the right amount of affection and love unconditionally and teaches a sense of responsibility and humanity in children. It alsoemphasises respecting the children and at the same time teaching them the basics of life without being pedantic. It is to be the child’sfriend and mentor without one role over powering the other. Parenting is one of the most fulfilling tasks in life, yet one of the most difficultones. Every parent deals with his/her child in their own different way, still most of the parenting types can be categorized into somespecific types of parenting. This paper will discuss the commonly found parenting types, their advantages and disadvantages. That are:the Authoritarian, democratic, permissive, desmissive, and abusive types. Two of these types will be discussed in this paper: thedemocratic and the abusive types as they are the subject of To Kill a Mockingbird. The moral-philosophical approach will be implied asthe most suitable approach to the novel.